2005
DOI: 10.1191/1352458505ms1188oa
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and multiple sclerosis: a meta-analysis

Abstract: Using meta-analytic procedures, this study involved a quantitative synthesis of the difference in physical activity among individuals with multiple sclerosis (MS) compared with nondiseased and diseased populations and then examined factors (i.e., moderators) that explain variation in the overall difference in physical activity. We searched MEDLINE, PsycINFO and Current Contents Plus using the key words physical activity, exercise and physical fitness in conjunction with multiple sclerosis; conducted a manual s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
323
0
6

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 463 publications
(354 citation statements)
references
References 21 publications
25
323
0
6
Order By: Relevance
“…In addition to managing the symptoms of MS, participants prioritised "to keep active" and "for mobility", despite the existing evidence which suggests that many pwMS are inactive [5,6]. These results from this current study illustrate that as a group their intention is to be active and was one of the prime drivers for engaging in exercise and physical activity.…”
Section: Insights Into the Reasons Why Pwms Engage In Exercise And Phmentioning
confidence: 52%
See 1 more Smart Citation
“…In addition to managing the symptoms of MS, participants prioritised "to keep active" and "for mobility", despite the existing evidence which suggests that many pwMS are inactive [5,6]. These results from this current study illustrate that as a group their intention is to be active and was one of the prime drivers for engaging in exercise and physical activity.…”
Section: Insights Into the Reasons Why Pwms Engage In Exercise And Phmentioning
confidence: 52%
“…Rehabilitation interventions such as exercise and physical activity have been shown to be beneficial in the management of symptoms and associated disability in people affected by MS [2][3][4]. Despite this, many people with MS (pwMS) report lower levels of physical activity and lead sedentary lifestyles [5,6]. Systematic reviews and meta-analyses demonstrated several benefits of exercise in pwMS including: improvement in muscle strength and fitness [4,7], balance [7], quality of life and depression [4,8], and positive effects on fatigue [7,9].…”
Section: Introductionmentioning
confidence: 99%
“…In a meta-analysis of physical activity levels characteristic of individuals with MS, Motl et al 20 found that people with MS are significantly less active than asymptomatic populations but are at least as active as other chronically diseased populations. It may not be appropriate, however, to use standard survey activity measures to directly compare diseased populations with asymptomatic populations.…”
Section: Activity Levels Of People With Ms and Exercise Recommendationsmentioning
confidence: 99%
“…Increasing the overall physical activity level of patients with MS is also crucial to maintaining long-term health in the population despite the inherent challenges to patients with MS in sustaining an increased activity level [45]. A meta-analysis performed by Motl et al outlined the current physical activity levels in patients with MS and found that they are less active than nondiseased populations [14]. In addition, patients with MS have lower QOL scores and lower levels of physical activity than other persons with chronic conditions [3,[9][10].…”
Section: Discussionmentioning
confidence: 99%
“…Increases in structured exercise participation and increases in physical activity levels have been shown to increase QOL scores [11][12][13]. Currently, physical activity levels in patients with MS are significantly lower than nondisabled groups [14]. However, evidence shows that patients with MS benefit from structured exercise [15].…”
Section: Introductionmentioning
confidence: 97%